Review of Equal Channel Angular Pressing System - Rajmane, Umesh C. (Asian Review of Mechanical Engineering, 2016)
Equal channel angular pressing (ECAP) is a forming procedure. The Equal Channel Angular Pressing is a hardening treatment with which ductile metals can be processed to refine their grain and sub-grain structure. This process enhances the mechanical strength of metals in terms of tensile strength, stress-controlled fatigue strength, and fatigue crack growth resistance. The Equal Channel Angular Pressing is a hardening treatment with which ductile metals can be processed to refine their grain and sub-grain structure. This process enhances the mechanical strength of metals in terms of tensile strength, stress-controlled fatigue strength, and fatigue crack growth resistance. In this review, underline some critical aspects that have to be more investigated.